A Global Radical Waterfront The International Propaganda Committee of Transport Workers and the International of Seamen and Harbour Workers, 1921-1937 - Weiss, Holger (Studies in Global Social History, 2021)
This volume investigates the ambition of the Red International of Labour Unions to radicalize the global waterfront during the interwar period. The main vehicle was the International Propaganda Committee of Transport Workers, replaced in 1930 by the International of Seamen and Harbour Workers as well as their agitation and propaganda centres, the International Harbour Bureaus and the International Seamen's Clubs. The book scrutinizes their solidarity campaigns in support of local and national strikes as well as on their agitation against discrimination, segregation and racism within the unions, their demands to organize non-white maritime transport workers, and their calls for engagement in anti-fascist, anti-war and anti-imperialist actions. Readership: All interested in global labour history and labour radicalism and militancy, the history of the Comintern/Red International of Labour Unions/Profintern, global history of the interwar period, history of antifascism, anti-imperialism, and anti-colonialism, as well as global maritime history.